2015
DOI: 10.1002/btpr.2135
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the release of bioactiveN-glycans from dairy products by a novel endo-β-N-acetylglucosaminidase

Abstract: Endo-β-N-acetylglucosaminidase isolated from B. infantis ATCC 15697 (EndoBI-1) is a novel enzyme that cleaves N-N′-diacetyl chitobiose moieties found in the N-glycan core of high mannose, hybrid, and complex N-glycans. These conjugated N-glycans are recently shown as a new prebiotic source that stimulates the growth of a key infant gut microbe, Bifi-dobacterium longum subsp. Infantis. The effects of pH (4.45–8.45), temperature (27.5–77.5°C), reaction time (15–475 min), and enzyme/protein ratio (1:3,000–1:333) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 32 publications
0
29
1
Order By: Relevance
“…14,15 Its activity is not affected by a fucosylated N -glycan core and it was also shown to be heat resistant, which enables use during 95°C heat treatments, in contrast to the currently available N -acetylglucosaminidases such as PNGase F. We recently demonstrated that temperature, pH, reaction time, and enzyme/protein ratio significantly affected the yield of released N -glycans by EndoBI-1. 16 In this work, we demonstrate that varying these conditions (pH, temperature, reaction time, and enzyme/protein ratio) affects the structural diversity of released N -glycans from bovine colostrum whey protein concentrate as determined by advanced mass spectrometry. This selective release of N -glycans from bovine colostrum whey glycoproteins allows for further study of their biological activity.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…14,15 Its activity is not affected by a fucosylated N -glycan core and it was also shown to be heat resistant, which enables use during 95°C heat treatments, in contrast to the currently available N -acetylglucosaminidases such as PNGase F. We recently demonstrated that temperature, pH, reaction time, and enzyme/protein ratio significantly affected the yield of released N -glycans by EndoBI-1. 16 In this work, we demonstrate that varying these conditions (pH, temperature, reaction time, and enzyme/protein ratio) affects the structural diversity of released N -glycans from bovine colostrum whey protein concentrate as determined by advanced mass spectrometry. This selective release of N -glycans from bovine colostrum whey glycoproteins allows for further study of their biological activity.…”
Section: Introductionmentioning
confidence: 77%
“…Signal peptide and transmembrane domains were not amplified to facilitate protein expression and purification from E. coli . Gene amplification and protein expression in E. coli BL21* strain were performed as described by Garrido et al 16 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Briefly, EndoBI-1 was incubated with concentrated bovine colostrum whey under conditions previously determined to be optimal for enzyme activity (pH 5, overnight, 37°C) (44). Cleavage was performed under nondenaturing conditions because the goal of this study was to produce the N-glycans in a native state and to preserve biological function.…”
Section: Resultsmentioning
confidence: 99%
“…We recently determined the optimal conditions and kinetic parameters of N-glycan release from concentrated bovine whey for large-scale N-glycan production using EndoBI-1 (13,44,45). In this work, EndoBI-1 treatment of milk glycoproteins demonstrated that freed glycans, as opposed to deglycosylated milk protein, are a good substrate for rapid and selective growth, similar to HMOs.…”
mentioning
confidence: 99%